Heritage asset disclosure framework (HADiF) 2.0 - Rosli, Mohamad Hafiz; Kamaluddin, Amrizah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Heritage Asset (HA) is unique and incomparable to other types of assets as it is significant to the country’s history, culture, social and environment. From an accounting perspective, the HA needs to be accounted for in the public sector financial statement in line with the implementation of accrual accounting under the New Public Management (NPM). Not only that, in the context of the world’s sustainability, the Sustainable Development Goals (SDG) 11 aims to strengthen the effort to protect and safeguard the world’s cultural and natural heritage. Thus, this has required special attention to be given to HA. The current reporting of HA provides rarer guidelines to the preparers, particularly in the valuation and presentation resulting in underreporting of HA. Heritage Asset Disclosure Framework (HADiF) provides a framework specifically for the reporting of HA in the Malaysian Public Sector that integrates both financial and non-financial disclosure information of HA to be reported. HADiF 2.0 detailed the ‘narrative component’ and disclosure items to be incorporated in the HA report. The enhancement of HA disclosure helps preparers to produce more useful and relevant information about HA and enables the public sector agencies to discharge their public accountability by providing more transparent disclosure. Eventually, the public could assess the HA information to appreciate the country’s HA better. Extensive disclosure of HA is able to reflect the value and significance of HA that primarily focuses on cultural and social values